Lumbar pseudomeningocele following blunt trauma without spinal fractures - Gonçalves da Silva, José Alberto; dos Santos Junior, Adailton Arcanjo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2013)
The lumbar pseudomeningocele (PSM) is an uncommon condition, mainly, after a lumbar blunt trauma. The authors present a rare case of PSM following a lumbar blunt trauma which did not show any abnormalities in the magnetic resonance imaging (MRI) of the lumbar region. Firstly, the patient underwent to conservative treatment that fail and then it was performed a surgical approach of the lumbar area, however, the lumbar fluid collection appeared again and a lumboperitoneal shunt (LPS) was then performed with complete successful. One year and half afterwards the LPS the patient continues asymptomatic. The standard treatment of this condition remains uncertain, but the conservative treatment followed by LPS is a good option and can be done in several cases.
Keywords: Meningocele; spinal injuries; lumbosacral region; fistula